Interhemispheric characterization of small vessel disease imaging markers after subcortical infarct. Issue 1 (3rd November 2016) - Valdés Hernández, Maria del C.; Qiu, Xinyi; Wang, Xin; Wiseman, Stewart; Sakka, Eleni; Maconick, Lucy C.; Doubal, Fergus; Sudlow, Cathie L. M.; Wardlaw, Joanna M.
Abstract: Background: In structural Magnetic Resonance Imaging (MRI) of patients with a recent small subcortical infarct (RSSI) and small vessel disease (SVD) imaging markers coexist. However, their spatial distribution and prevalence with respect to the hemisphere of the RSSI remain unknown. Materials and Methods: From brain MRI in 187 patients with an acute lacunar ischemic stroke clinical syndrome and a relevant diffusion weighted imaging (DWI)‐positive lesion, we semiautomatically extracted the RSSI, microbleeds, lacunes, old cortical infarcts, and white matter hyperintensities (WMH) using optimized thresholding in the relevant sequences, and rated the load of perivascular spaces. We registered all images to an age‐relevant brain template and calculated the probability distribution of all SVD markers mentioned for patients who had the RSSI in each hemisphere separately. We used the Wilcoxon and chi‐squared tests to compare the volumes and frequencies of occurrence, respectively, of the SVD markers between hemispheres throughout the sample. Results: Fifty‐two percent patients ( n  = 97) had the RSSI in the left hemisphere, 42% ( n  = 78) in the right, 2.7% ( n  = 5) in both, and 3.7% ( n  = 7) in the cerebellum or brainstem. There was no significant difference in RSSI frequency between left and right hemispheres ( p  = .10) in the sample. The median volume of the RSSI (expressed as a percentage of the total intracranial volume) was 0.05% (IQR = 0.06). There was no difference in median percent volume of the right RSSIs versus left ( p  = .16). Neither was there a significant interhemispheric difference in the volume of any of the SVD markers regardless of the location of the RSSI and they were equally distributed in both hemispheres. Conclusion: Assessment of SVD imaging markers in the contralateral hemisphere could be used as a proxy for the SVD load in the whole brain to avoid contamination by the RSSI of the measurements, especially of WMH. Abstract : We report the spatial distribution and prevalence of small vessel disease imaging markers with respect to the location of the recent subcortical infarct on 187 patients who had an acute ischemic stroke clinical syndrome and a relevant DWI‐positive lesion. The MRI scan was obtained in the interval between stroke onset and 4 weeks after. There was no difference in median percent volume of the right RSSIs versus left ( p  = .16). Neither was there a significant interhemispheric difference in the volume of any of the markers regardless of the location of the infarct and they were equally distributed in both hemispheres.